A Form of Independent Curriculum, an Overview of Independent Learning at State Elementary School 05 Gelumbang Muaraenim - Mustafiyanti Mustafiyanti; Mesi Pramesia Putri; Muyassaroh Muyassaroh; Dwi Noviani; Moatti Dylan (Yayasan Adra Karima Hubbi, 2023)
Background. The Merdeka Curriculum as an alternative curriculum overcomes learning setbacks during the pandemic which gives